Are All Remote Associates Tests Equal? An Overview of the Remote Associates Test in Different Languages - Behrens, Jan Philipp; Olteţeanu, Ana-Maria (Frontiers in Psychology, 2020)
The Remote Associates Test (RAT, CRA) is a classic creativity test used to measure creativity as a function of associative ability. The RAT has been administered in various different languages. Nonetheless, because of how embedded in language the test is, only a few items are directly translatable, and most of the time, the RAT is created a new in each language. This process of manual (and in two cases, computational) creation of RAT items is guided by the researchers' understanding of the task. This paper focuses on the question of whether RAT datasets administered in different languages within the literature are comparable. To answer this question, datasets acquired using different RAT stimuli are analyzed qualitatively and quantitatively. Kruskal-Wallis tests are conducted to find out whether there is a significant difference between any of the datasets for a given time frame. Pairwise Mann-Whitney post-hoc tests are then used to find out which pairs are different. Significant differences are observed between 18 dataset pairings regarding Accuracy and between 16 in terms of Response Time. The potential sources of these differences are discussed, together with what this means for creativity psychometrics and computational vs. manual creation of stimuli.